Harmonisasi Pancasila dan Nilai Keislaman dalam Implementasi Karikulum PKN di Lingkungan Pendidikan Indonesia - Sera Sera; Syamzaimar Syamzaimar (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2026)
This journal critically examines the process of harmonizing Pancasila values and Islamic principles within the development of the Citizenship Education (PKn) curriculum in Indonesia. The study aims to understand how the integration of these two values can strengthen national character, enhance tolerance, and enrich the learning process at elementary and secondary school levels. The methodology used is a literature review, analyzing various academic sources, curriculum documents, and theoretical studies related to the harmonization of national and religious values. The findings indicate that applying the principle of harmonization can improve students’ understanding of Pancasila and Islamic values simultaneously, as well as foster mutual respect and appreciation for Indonesia’s cultural and religious diversity. These results underscore the importance of incorporating these values into the PKn curriculum as a strategic effort to build a nation grounded in spiritual, nationalist, and tolerant values. Additionally, this research offers recommendations for developing a more inclusive and harmonious curriculum to create a tolerant, civil, and respectful society.